Advanced Composite of Large Cell Neuroendocrine Carcinoma and Squamous Cell Carcinoma: A Case Report of Uterine Cervical Cancer in a Virgin Woman - Ryusuke Murakami; Iemasa Kou; Kenjiro Date; Hirofumi Nakayama (Case Reports in Obstetrics and Gynecology)
Large cell neuroendocrine carcinoma (LCNEC) of the uterine cervix is very rare and aggressive. The prognosis is very poor despite multimodal treatment. We report a virgin woman with FIGO stage 4b LCNEC of uterine cervix coexisting with squamous cell carcinoma. An early thirties virgin woman presented with 2-month history of abdominal pain. A chest X-ray showed multiple lung metastatic tumors. A vaginal smear showed malignant cells, and a biopsy specimen had features of LCNEC. The tumor showed trabecular patterns. Tumor cells possessed a moderate amount of cytoplasm, prominent nucleoli, and large nuclei. The tumor cells are stained positive for synaptophysin, chromogranin A, and neuron specific enolase (NSE). The invasive tumor cells in connection with cervical squamous epithelium were focally positive for 34bE12. We made a diagnosis of composite LCNEC and nonkeratinizing squamous cell carcinoma. High-risk HPV test was negative with hybridized captured method 2.